Utilization Of Solar Energy In Iot-Based Seawater Desalination Equipment In National Energy Security - M Raafi Aqil Firdaus; Novky Asmoro; Sri Murtiana (International Journal of Technology and Education Research, 2026)
Lack of clean water supply has become a serious problem in many coastal areas. In an effort to overcome this problem, seawater desalination is one of the possible solutions. In relation to this problem, this paper proposes an innovative approach combining seawater desalination with solar energy technology and IoT to provide clean water efficiently and sustainably. This system uses solar energy as the main power source to drive the desalination process. Sensors connected to the IoT network are used to measure important parameters such as water temperature and EC that enable real-time monitoring. However, the results of the desalination process still leave harmful waste compounds such as lead and iron, so it is necessary to re-filtrate with natural adsorbents zeolite and activated carbon. Based on the results of measurements and calculations, a solar power plant capacity of 40.821 Wp is needed and a battery capacity of 790.815 Ah